(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
As is known, at present the use of static and dynamic equations alone is insufficient for solving the problem of equilibrium of agricultural units. It becomes necessary to introduce additional forces, which significantly increases the complexity of research in this field. Existing studies are characterized by the fact that when analyzing the stability of a tillage implement based on equilibrium conditions, the standard plow body is considered as the working tool.